The Impact of the Hippie Movement on Modern American Lifestyle - Belkhiri ,Nail; Kaid , Nassima (Faculty of Letters and Foreign Languages Department of English, 2018)
This present dissertation aims to examine the impact of the Hippie movement on the modern American lifestyle in general. It will be based on gathered data and analyses of the emergence of this movement and its impact and influence on Americans by the genuine peaceful and lovable behaviors the Hippies have. The study begins from the movement’s birth as small gatherings, until the full composition of the whole echoing movement. The initial phase of the study tackles the background of the Hippies, starting from the 1940s Baby Boomers. However, by the use of the gathered data, there came the chance of spotting all aspects related to the coming 1950s, including the birth of the Beat movement; and delving into reaching the arrival of 1960s when the Hippie movement was considered official and at its peak. Taking into consideration the detailed information provided through various methods of research all along this study, there are many different inceptions and points of view gathered from several sources, about the progress of the Hippie movement all along the American chronicle, for the purpose of extending the pack of knowledge considering the Hippies and their history. As for the reverberated results from the study, the Hippies were certainly a movement that still has an impact on the people’s views toward life. They could reflect the sense of sharing, loving and caring for everyone. They stood against their government’s decisions concerning foreign affairs and military involvements. They were able to even affect art, fashion and social attitudes, through what they have fought for since their very first beginning. People became more interested in embracing nature and tolerating others, thanks to the Hippies who were seen as reckless, uninterested youth protestors